Electronic Security : Risk Mitigation in Financial Transactions - Public Policy Issues - Glaessner, Thomas; Kellermann, Tom; McNevin, Valerie (World Bank, Washington, DC, 2014)
This paper builds on a previous series of papers (see Claessens, Glaessner, and Klingebiel, 2001, 2002) that identified electronic security as a key component to the delivery of electronic finance benefits. This paper and its technical annexes (available separately at http://www1.worldbank.org/finance/) identify and discuss seven key pillars necessary to fostering a secure electronic environment. Hence, it is intended for those formulating broad policies in the area of electronic security and those working with financial services providers (for example, executives and management). The detailed annexes of this paper are especially relevant for chief information and security officers responsible for establishing layered security. First, this paper provides definitions of electronic finance and electronic security and explains why these issues deserve attention. Next, it presents a picture of the burgeoning global electronic security industry. Then it develops a risk-management framework for understanding the risks and tradeoffs inherent in the electronic security infrastructure. It also provides examples of tradeoffs that may arise with respect to technological innovation, privacy, quality of service, and security in designing an electronic security policy framework. Finally, it outlines issues in seven interrelated areas that often need attention in building an adequate electronic security infrastructure. These are: 1) The legal framework and enforcement. 2) Electronic security of payment systems. 3) Supervision and prevention challenges. 4) The role of private insurance as an essential monitoring mechanism. 5) Certification, standards, and the role of the public and private sectors. 6) Improving the accuracy of information on electronic security incidents and creating better arrangements for sharing this information. 7) Improving overall education on these issues as a key to enhancing prevention.